A tiny new species of Specklinia from Haiti’s Parc National Naturel Macaya and new combinations in Acianthera (Pleurothallidinae, Epidendreae, Epidendroideae, Orchidaceae) - Doucette, Alfonso; Timyan, Joel; Henrys, Ingrid; Cameron, Kenneth M. (Phytotaxa, 2016)
A new species of Specklinia with a repent growth habit and minute purple flowers is described and illustrated. The new species is distinguished from Specklinia wrightii based on its morphological and molecular distinctness from that species. The phylogenetic placement of the new species is provided based on an nrITS tree. The species described here represents the first new orchid to be described from material originating from the Parc National Naturel Macaya in six years. New combinations are made in Acianthera for species of Kraenzlinella and Pleurothallis subgen. Antilla embedded within the genus. In particular Kraenzlinella rinkei is provided as a new synonym for Specklinia montezumae and Specklinia simpliciflora is transferred to Acianthera sect. Antilla based on morphology and geographic distribution.